Overcoming Student Apathy: Motivating Students for Academic Success - Marshall, Jeff C. (Rowman & Littlefield Publishers, 2008)
Overcoming Student Apathy: Motivating Students for Academic Success provides a candid look into the hearts and minds of many of today's struggling students. Frustrated teachers and administrators typically stop at labeling the symptoms shown by these students: apathy, low motivation, laziness. Overcoming Student Apathy clarifies the situation, while proposing tips to rise to the challenge. Apathy plagues many of today's middle and high school classrooms, and the problem will not spontaneously disappear. Teachers must be willing to move beyond the 'they don't care' attitude to discover how we can eradicate this nemesis to learning. Overcoming Student Apathy guides the reader toward success with the disenfranchised, the downtrodden, the devalued, and the demoralized. Eight archetypes are used in narrative form to represent the various forms that apathy assumes in our classrooms (e.g., The Rebel, The Downtrodden, The Invisible). Teachers will identify with both the students and the teachers portrayed in the book; thus, transferring understanding and applications back to their own classrooms.